2007
DOI: 10.1002/cncr.22589
|View full text |Cite
|
Sign up to set email alerts
|

Male breast cancer in the veterans affairs population

Abstract: BACKGROUND. The incidence of male breast cancer (MBC) continues to rise. The Veterans Affairs (VA) Central Cancer Registry (VACCR) provides a unique source for the study of MBC. The objective of this retrospective analysis was to compare the characteristics and outcome of patients with MBC and patients with female breast cancer (FBC) in the VA population. METHODS. VACCR data were used to analyze the database of VA patients who had breast cancer diagnosed between 1995 and 2005. It includes 120 VA medical center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
91
3
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(108 citation statements)
references
References 17 publications
10
91
3
4
Order By: Relevance
“…It is noteworthy that two of the four BRCA1 mutation carriers found in our series harbor the same mutation that was previously identified as a founder mutation in Central Italy [17]. Compared with previous studies, in our series age at diagnosis was lower and the percentage of cases with a positive first-degree FH was higher [18][19][20][21]. This could reflect the presence of MBC patients enrolled in a context of genetic counselling programs, which are more frequently characterized by familial cancer and younger age at diagnosis.…”
Section: Discussionsupporting
confidence: 52%
“…It is noteworthy that two of the four BRCA1 mutation carriers found in our series harbor the same mutation that was previously identified as a founder mutation in Central Italy [17]. Compared with previous studies, in our series age at diagnosis was lower and the percentage of cases with a positive first-degree FH was higher [18][19][20][21]. This could reflect the presence of MBC patients enrolled in a context of genetic counselling programs, which are more frequently characterized by familial cancer and younger age at diagnosis.…”
Section: Discussionsupporting
confidence: 52%
“…Given the rarity of the disease, most of the information regarding its characteristics, management and outcome is based on either retrospective studies of a small number of patients or extrapolation of the results of female breast cancer (FBC). (Giordano et al, 2004;Nahleh et al, 2007;Sedighi et al, 2013) Recently published data in the United(surgery, chemotherapy and radiotherapy), and outcome (follow up, recurrence and five year survival).…”
Section: Introductionmentioning
confidence: 99%
“…Male breast cancer has been reported between the ages of 5 and 93 years, with a median age of 68 years (14)(15)(16)). In our current study, the ages of the patients with MBC ranged between 32 and 79 years (mean age: 63 years).…”
Section: Discussionmentioning
confidence: 99%
“…Axillary lymph node involvement is the strongest predictor of both metastatic and local recurrence risk; it is present in about 50% MBCs (4,14,40). It has been reported that there are more than three nodes involved in approximately 40% of patients with nodal involvement (4,41).…”
Section: Discussionmentioning
confidence: 99%